ANALISIS UNSUR-UNSUR INTRINSIK CERPEN “SENYUM KARYAMIN” KARYA AHMAD TOHARI - Dewi Nurcahyati; Ai Yulianti; Dede Abdurrokhman (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This study examines the intrinsic elements of the short story entitled "Senyum Karyamin" by Ahmad Tohari. Aim to meganalisis, describe, and interpret the intrinsic elements in the short story "Senyum Karyamin". The analysis uses a structural approach. Intrinsic elements or building elements in which are discussed are facts that exist in the short story and consist of themes, backgrounds, lines, points of view, figures, officers and then mandates. Research in the short story "Senyum Karyamin" uses a qualitative descriptive research method that uses a structural approach. A structural approach is an approach in the science of literature by the way it works to analyze the elements and structures that build literary works from within the story and look for the interrelationships of these building elements to achieve roundness of meaning. Processing data to use structural analysis techniques, short story intrinsic elements by identifying by reading and taking notes. Identify themes, plots, characterizations, backgrounds, perspectives, language styles and write footage taken from "Senyum Karyamin" stories. To analyze by interpreting the contents of the snippet taken from the "Senyum Karyamin" short story, reviewing or analyzing more in the contents of the snippet and describing it. From the results of the analysis, there are intrinsic elements in the short story "Senyum Karyamin", namely the theme, character, plot, setting, point of view, character and mandate clearly conveyed. In analyzing the intrinsic elements of "Senyum Karyamin" short stories can be used as a motivation for the reader.